High temperature advanced materials - Tan, Ming Jen. (2008)
Superplasticity is the capability to deform crystalline solids in tension to unusually large plastic strains, often well in excess of 1000%. This phenomenon results from the ability of the material to resist localized deformation much the same as hot glass does. As high elongations are possible, complex contoured parts can be formed in a single press cycle often eliminating the need for multipart fabrications. This enables the designer to capture several detail parts into a one piece complex, formed structure. Thus materials with superplastic properties can be used to form complex components in shapes that are very near the final dimension. Superplastic forming also enhances design freedom, minimizes the amount of scrap produced, and reduces the need for machining. In addition, it reduces the amount of material used, thereby lowering overall material costs. Work reported here looks into the High Temperature Deformation and Superplasticity of difficult-to-form materials, viz. (i) Metal Matrix Composites, (ii) Titanium Alloy, in particular, Ti-6Al-4V and commercial purity titanium. The work studies the processing, mechanical properties, microstructural character, evolution and manipulation for the high performance of these materials. The degradation of these properties in Titanium alloys due to prolonged high temperature exposure and the effects of oxidation prevention is also studied. In addition, because most of these difficult-to-form materials suffer from cavitation during SPF, which will lead to the degradation of the overall properties of the post-SPF materials, simulation of superplastic sheet forming for cavity sensitive material has been studied together with the analysis of the influence of various factors on the cavitation process. The effects of strain rate sensitivity, cavity growth and imposed hydrostatic pressure on the strain limits are studied. The predicted results are validated through the comparison with the existing experimental data.